E-cadherin adhesion molecule and syndecan-1 expression in various thyroid pathologies - Mitselou, A.; Ioachim, E.; Peschos, D.; Charalabopoulos, K.; Michael, M.; Agnantis, N.J.; Vougiouklakis, T. (Experimental Oncology, 2007)
Cadherins and syndecans are transmembrane glycoproteins implicated in cell-cell and cell-matrix adhesion. Impairment of cadherin and syndecan mediated adhesion is likely to constitute one of the main factors leading to the reduced cell-cell and cell-matrix adhesion characteristics of tumor cells and play a pivotal role in the acquisition of invasive and metastatic proprieties by neoplastic epithelial cells. Aim: To elucidate the role and alterations of syndecan-1 expression in comparison with those of E-cadherin in normal and pathological thyroid glands (TG). Methods: A total of 55 TG carcinomas, 40 TG adenomas, 40 cases of hyperplastic TG disorders and 20 cases of normal TG autopsy samples, were evaluated by immunohistochemistry. The staining intensity, and localization of syndecan-1 and E-cadherin in sequential sections were examined, and semi-quantified. Results: Immunostaining of syndecan-1 and E-cadherin was strong in normal follicular TG epithelial cells, and located mainly in basolateral membrane. No significant change was seen in either molecule in hyperplastic TG disorders compared with TG adenomas. A significant reduction in expression of both syndecan-1 and E-cadherin was seen in well-differentiated TG carcinomas as compared with normal TG epithelium (p = 0.0001 and p = 0.032, respectively). Similarly, there was a significant reduction of both molecules expression in poorly differentiated and anaplastic TG carcinomas compared to well differentiated tumors (syndecan-1: p = 0.0037; and E-cadherin: p = 0.075). Conclusion: Decreased E-cadherin and syndecan-1 expression along with decreasing cellular differentiation may be involved in the complex mechanism of progression of TG pathology.